The Evolving Role of Allogeneic Stem Cell Transplant in the Era of Molecularly Targeted Agents. Issue 1 (January 2022) - Kinsella, Francesca; Craddock, Charles
Abstract: Allogeneic stem cell transplantation (allo-SCT) is an increasingly important treatment strategy in fit adults with acute myeloid leukemia (AML). Increased donor availability and a steady reduction in transplant-related mortality (TRM) over the last 2 decades have transformed access to the curative potential of allo-SCT. The identification of patients with AML in first complete remission who will benefit from allo-SCT requires a dynamic assessment of the risk of disease relapse and TRM. Increased accuracy in predicting both relapse risk and transplant toxicity has allowed recommendations for allo-SCT to become increasingly personalized. Notwithstanding its now central position in the treatment algorithm of patients with AML, there, however, has been little progress in reducing the main cause of transplant failure, which remains disease relapse. Novel molecularly targeted therapies have the potential to augment the curative potential of nontransplant therapies, and this may influence the proportion of newly diagnosed fit patients deemed to be allomandatory. At the same time, the ability of such therapies to improve transplant outcomes, either by reducing TRM or the risk of relapse, has the potential to further embed allo-SCT as a key therapeutic modality in AML.